Heat acclimation/acclimatization and associated nutrition practices: a survey to determine practitioner and elite athlete knowledge and use (should we be concerned?) - Taylor, L.; Galán-López, N.; Hill, T.; James, L.; Chrismas, B.; Racinais, S.; Stellingwerff, T.; Leal, D.; Hausen, M.; Chamari, K.; Fullagar, H.; Esh, C.; et al. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Heat acclimation/acclimatization (HA) is the principal and most effective intervention to protect athletes from heat-mediated performance decrements and provide some protection against heat illnesses when exercise is performed in thermally challenging environments. That said, relatively little is known regarding how centuries worth of data in these regards, penetrates the knowledge and practice of elite athletes and practitioners. With the ever-increasing globalization of sport on a consistently warming planet, elite sport, including mega events, are increasingly held in such thermally challenging environments (e.g., Tokyo 2020ne). Thus, practitioners and their athletes alongside policy makers have a responsibility to prepare their athletes appropriately and educate their members, respectively. Additionally, the events themselves require diligent infrastructural and logistical preparation to deliver evidence-informed performance-facing support and potentially life-saving medical services. Therefore, the purpose was to survey elite athletes and practitioners to identify: (i) knowledge and application of heat acclimation/acclimatization (HA) interventions; (ii) barriers to HA application; and (iii) nutritional practices supporting HA.